Innovations in telemedicine for cardiovascular care - Brunetti, Natale Daniele; Scalvini, Simonetta; Molinari, Giuseppe (Expert review of cardiovascular therapy, 2016)
Cardiovascular disease is one of the main fields of application for telemedicine, with benefits in almost all areas in the continuum of cardiovascular disease. The greatest impact has been shown in the early diagnosis of cardiovascular disease, in second consultation, between non-cardiologist and cardiologist and between cardiologists, and in follow-up and secondary prevention of cardiovascular disease. At present, the main area of implementation for telemedicine in cardiovascular disease is represented by pre-hospital triage, with telemedicine electrocardiogram in acute myocardial infarction. Significant results have also been achieved in the second opinion consultation of pediatric subjects with congenital cardiovascular disease, home-monitoring and the management of patients affected by chronic heart failure or with an implanted device. However, there is significant room for further improvement in delivering telemedicine assistance even in 'very-remote' populations, such as detainees, patients in developing countries or in underdeveloped areas of developed countries.